2017
DOI: 10.19182/bft2016.330.a31320
|View full text |Cite
|
Sign up to set email alerts
|

Cartographie De La Dynamique De Terroirs Villageois À L’aide D’un Drone Dans Les Aires Protégées De La République Démocratique Du Congo

Abstract: Les aires protégées de la République démocratique du Congo (RDC) sont mena-cées par diverses pressions anthropiques nécessitant un suivi fréquent et précis. Le mini-drone Falcon équipé d’un appareil photo numérique Sony NEX-7 a été utilisé pour cartographier et suivre la dynamique d’un terroir villageois dans le Domaine de chasse de Mondo Missa à l’est du Parc national de la Garamba, au nord-est de la RDC. Un total de 3 143 photos acquises en avril et juillet 2015, avec une résolution au sol de 8 cm/pixel, a é… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
1
8
0
1
Order By: Relevance
“…The fallow crop and built-up areas gained surface area significantly. These results corroborate those found by other authors (Bamba 2010;Dejace 2019;Rageade 2014) in the Luki region and elsewhere (Katembera et al 2015;Opelele et al 2020;Useni et al 2020;Ngabinzeke et al 2016;Megevand 2013;Potapov et al 2012) who argue that population growth and expansion increase cultivated area expansion as well as the degradation of natural ecosystems leading to the conversion of primary forest into a mosaic of secondary forest and savanna. The research conducted by Bamba (2010) also mentioned that the decrease in forest area is due to the unsustainable agricultural system and demographic pressure.…”
Section: Lulc Change Assessmentsupporting
confidence: 91%
See 1 more Smart Citation
“…The fallow crop and built-up areas gained surface area significantly. These results corroborate those found by other authors (Bamba 2010;Dejace 2019;Rageade 2014) in the Luki region and elsewhere (Katembera et al 2015;Opelele et al 2020;Useni et al 2020;Ngabinzeke et al 2016;Megevand 2013;Potapov et al 2012) who argue that population growth and expansion increase cultivated area expansion as well as the degradation of natural ecosystems leading to the conversion of primary forest into a mosaic of secondary forest and savanna. The research conducted by Bamba (2010) also mentioned that the decrease in forest area is due to the unsustainable agricultural system and demographic pressure.…”
Section: Lulc Change Assessmentsupporting
confidence: 91%
“…The clearing in the secondary forests being partial. Agriculture is essentially practiced in the undergrowth while maintaining the status of secondary forest (Ickowitz et al 2015;Ngabinzeke et al 2016). This leads more to degradation than deforestation of the secondary forest impeding its evolution towards a mature forest and a significant encroachment into the primary forest (Peltier et al 2014).…”
Section: Human-induced Fire Impacts On Lulc Changesmentioning
confidence: 99%
“…Several studies have shown that urban expansion and population growth are at the root of the problems associated with heat islands [80][81][82], the increase in carbon emissions, and the loss of carbon [83]. In the Democratic Republic of Congo, several studies have revealed that population growth and urban expansion increases the proliferation of cultivation areas as well as the degradation of natural ecosystems [23,[84][85][86][87]. Indeed, many natural land use types have been converted into crop, plantation, and degraded areas due to economic benefits.…”
Section: Land Use Change Of the Luki Biosphere Reservementioning
confidence: 99%
“…La déforestation ou la dégradation des forêts sont généralement évaluées à l'aide d'outils de télédétection à haute résolution spatiale (Molinario et al, 2015), voire, plus localement, à l'aide d'imageries à très haute résolution (Semeki Ngabinzeke et al, 2016). L'acquisition de ces données nécessite l'engagement de coûts financiers élevés (Willis, 2015).…”
Section: Introductionunclassified